2022
DOI: 10.52380/ijpes.2022.9.2.529
|View full text |Cite
|
Sign up to set email alerts
|

School Burnout in Middle School Students: Role of Problem Solving Skills, Peer Relations and Perceived School Experiences

Abstract: Purpose: The purpose of this study is to examine the relationships between middle school students' school burnout, problem-solving skills, peer relationships, and perceived school experiences and to determine the predictive power of perceived school experiences, problem-solving skills, and peer relationships on academic burnout. Method: The research was created based on the survey model. The sample of the study composed of 2538 secondary school students (1257 girls and 1281 boys) who attended ten official seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Low levels of social justice leadership have been connected to lower academic performance, school alienation, and a negative moderating effect on school burnout (Özdoğan Özbal, 2019). School burnout has also been demonstrated to have a negative moderating effect on the connection between academic pressure and school experiences (Güler & Bedel, 2022). In this review, the association between final test grade and overall school performance grew as the degree of school burnout increased.…”
Section: Moderating Relationshipsmentioning
confidence: 81%
See 3 more Smart Citations
“…Low levels of social justice leadership have been connected to lower academic performance, school alienation, and a negative moderating effect on school burnout (Özdoğan Özbal, 2019). School burnout has also been demonstrated to have a negative moderating effect on the connection between academic pressure and school experiences (Güler & Bedel, 2022). In this review, the association between final test grade and overall school performance grew as the degree of school burnout increased.…”
Section: Moderating Relationshipsmentioning
confidence: 81%
“…These studies concentrated on the association between school burnout and academic achievement or academic well-being (Çam & Ögülmüs, 2021;Gabola et al, 2021;Güler & Bedel, 2022, Güngör ,2019Martos Martínez et al, 2021;Özhan & Yüksel, 2021;Parviainen et al, 2021;Rimpelä et al, 2020;Savi Cakar & Uzun, 2021;Teuber et al, 2021;Tomaszek & Muchacka-Cymerman, 2020;Widlund et al, 2020;Yildirim & Koçak, 2022).…”
Section: Correlational Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key responsibilities of school-going children are to follow and attend classes structured by the school. Correspondingly, another study has confirmed that too much engagement in academic-oriented activities significantly predicts children's burnout (38). Thus, teachers, who spend much time with children at school and play an important direct role in the happiness of children, need to adequately reconsider class schedules, daily school routines, and the quantity of homework assigned to ensure that children have more free time to play every day.…”
Section: Discussionmentioning
confidence: 99%